English-Afrikaans Bilingual Building Dictionary - Pierre Oosthuizen (Town and Regional Planning, 2021)
With originating roots scattered across the globe, this playful language derived its name from Africa. What is more unique to South Africa than Afrikaans? A communication medium amalgamated, adapted and applied by mothers from different cultures and continents who not only chose South Africa as their domicilium citandi et executandi, but also to raise their children through a unique South African mother tongue. By accommodating variety, this language tends to be inclusive against the norm, which might explain why Afrikaans is the preferred lingua franca in many parts of the country. Since the tower of Babel, building sites are recognised as a gathering of miscellaneous cultures and languages in dire need for a bridging communication medium. Phenomenally, evolved through time, building terms were and still are being born.